Analysis of Islamic Bank Marger Policy in the Profitability Level of Indone-sian Islamic Bank, Kutacane Branch Office - Hafizah, Raisya; Anggraini, Tuti; Inayah, Nurul (LEGAL BRIEF, 2025)
This study aims to analyze the influence of merger policy on bank profitability levels with a case study at Bank Syariah Indonesia (BSI) Kutacane Branch Office. Since the merger of several national Islamic banks into one entity, namely BSI, there have been various changes in both operational and financial performance. One important indicator that is the focus of attention is profitability, which is measured by Return on Assets (ROA), Return on Equity (ROE), and profit margin. This study uses a quantitative approach with descriptive and comparative analysis methods. Data were taken from the financial statements of BSI KC Kutacane before and after the merger, and analyzed using a comparative method. The results of the study indicate that there are significant changes in the level of profitability post-merger. Factors such as operational efficiency, increasing the number of customers, and synergy between business units contribute to increased profitability. However, challenges in adjusting management and system integration also have a temporary impact on several financial indicators. The conclusion of this study shows that the merger policy has a positive impact on long-term profitability, although it requires adjustment and good management in the early stages after the merger. The recommendation given is to increase the focus on optimizing services and managing risks to maintain a positive trend in profitability in the futur